2022
DOI: 10.2147/opth.s378583
|View full text |Cite
|
Sign up to set email alerts
|

IgG4-Related Dacryoadenitis in Egyptian Patients: A Retrospective Study

Abstract: To report clinical, serological, and histopathological findings in Egyptian patients with dacryoadenitis associated with ImmunoglobulinG4-related disease (IgG4-RD). Methods: We retrospectively revised medical records of patients presented to Al-Azhar University Hospitals with lacrimal gland (LG) swelling between June 2016 and February 2022. We included patients with definite IgG4-related disease (IgG4-RD) diagnosis and excluded those with possible, probable, or unlikely IgG4-RD based on The Japanese Ministry o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Recently, a study showed that the IgG4/IgG ratio was correlated with the number of IgG4-positive plasmacyte in pathological tissues [21], suggesting that the IgG4/IgG ratio may be useful for diagnosing IgG4-RD. This study revealed that when other AID patients and healthy individuals were used as control groups, the areas under the ROC curve for IgG4/IgG ratio in diagnosing IgG4-RD amounted to 0.906 (95% CI, 0.865-0.947) and 0.921 (95% CI, 0.876-0.965).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study showed that the IgG4/IgG ratio was correlated with the number of IgG4-positive plasmacyte in pathological tissues [21], suggesting that the IgG4/IgG ratio may be useful for diagnosing IgG4-RD. This study revealed that when other AID patients and healthy individuals were used as control groups, the areas under the ROC curve for IgG4/IgG ratio in diagnosing IgG4-RD amounted to 0.906 (95% CI, 0.865-0.947) and 0.921 (95% CI, 0.876-0.965).…”
Section: Discussionmentioning
confidence: 99%